PERANAN SEKOLAH RUMAH TERHADAP PENINGKATAN MUTU PENDIDIKAN - Wartomo Wartomo (Universitas PGRI Yogyakarta, 2019)
AbstractChildhood maturation can develop perfectly can be taken through formal education institutions. Thus, other institutions need to be, as alternative institutions, including Home Schools. This can be developed as an alternative institution to improve education quality. Home School is formally valid, because based on Republic of Indonesia Law Number 20 of 2003, concerning the National Education System, namely the informal education pathway, and based on the Republic of Indonesia Minister of Education and Culture Regulation Number 129 of 2014, concerning Home Schools. While the form of Home School is: (1) Home School, (2) Compound Home School, and (3) Community Home School. Home Schools can determine the desired teacher themselves according to the purpose of establishing a Home School. Also the learning system tends to be individual and small group systems. Professional teachers who can know psychologically the talents, interests, and abilities of students, as well as individual or small group learning systems can better guarantee opportunities and the possibility of success in quality education can be achieved. Parents are advised to determine the teacher, really based on their professionalism in learning, and using individual systems, which pay more attention and provide broad opportunities for students to develop their talents, interests, and abilities.Keywords: Home School, Education, Quality